Study guides

☆☆

Q: What is the answer to 9p plus 2t-2p plus 3t?

Write your answer...

Submit

Still have questions?

Related questions

9p + 12

-9p + 6p = -3p

-10 -7 + 9p = 9p - 17

9(9p + 5r)(9p + 5r)

Plus 3T

9p + 27 = 9(p + 3)

3t+11 = 29 3t = 29-11 3t = 18 t = 6

Evaluate 9p + 33 for p = 5

-3t

20t

If you mean: 9t^2 +12t +4 then it is (3t+2)(3t+2) when factored

if you mean T-3t+2t+4 (T and t is different variables):T-3t+2t+4=T-t+4if you mean t-3t+2t+4:t-3t+2t+4=4

-14 + 3p = -9p - 21 add 14 and 9p to both sides, then 12p = -7 p = -7/12

9t2

4

3t - 1

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3

5t + 1

3t + 7 = 2t - 5 3t = 2t - 12 t = -12

s = 7, t = -3

9p - 5

2p+7p = 9p simplified

7s + 4t

Commutatitivity of addition in the fact that you can change the order of 11s and 3t. But also associativity of addition in that you can write the sum of three terms without the need for brackets to show which addition needs to be performed first.